Galangin Exhibits Neuroprotective Effects in 6-OHDA-Induced Models of Parkinson's Disease via the Nrf2/Keap1 Pathway - Qiu-Xu Chen; Ling Zhou; Tao Long; Da-Lian Qin; Yi-Ling Wang; Yun Ye; Xiao-Gang Zhou; Jian-Ming Wu; An-Guo Wu (MDPI AG, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease, and there is still no cure for it. PD is characterized by the degeneration of dopaminergic neurons, and oxidative stress has been considered an important pathological mechanism. Therefore, the discovery of antioxidants to alleviate the oxidative damage of dopaminergic neurons is a promising therapeutic strategy for PD. First, a network pharmacology approach was used, and nine common core targets of galangin and PD were screened, mainly involving cell aging, apoptosis, and cellular responses to hydrogen peroxide and hypoxia. In addition, the Gene Ontology (GO) function and pathway enrichment analysis of the Kyoto Encyclopedia of Genes and Genomes (KEGG) identified apoptosis, PI3K/Akt, and HIF-1 signaling pathways. Furthermore, the molecular docking results revealed a strong affinity between galangin and the NFE2L2/Nrf2 protein. To validate the above predictions, we employed 6-hydroxydopamine (6-OHDA) to induce neuronal death in HT22 cells and Caenorhabditis elegans (C. elegans). MTT, cell morphology observation, and Hoechst 33342-PI staining results showed that galangin significantly increased the viability of 6-OHDA-treated HT22 cells. In addition, galangin inhibited 6-OHDA-induced ROS generation and apoptosis in HT22 cells. Mechanistic studies demonstrated that galangin activates the Nrf2/Keap1 signaling pathway, as evidenced by the decreased protein expression of Keap1 and increased protein expression of Nrf2 and HO-1. In the 6-OHDA-induced PD model of C. elegans, galangin indeed inhibited the degeneration of dopaminergic neurons, improved behavioral ability, and decreased ROS generation. In conclusion, the current study is the first to show that galangin has the capacity to inhibit neuronal degeneration via the Nrf2/Keap1 pathway, suggesting that galangin is a possible PD treatment.